Disassociated feathers in Burmese amber shed new light on mid-Cretaceous dinosaurs and avifauna - Xing, Lida; Cockx, Pierre; McKellar, Ryan C. (Gondwana research, 2020)
Even in the absence of associated skeletal material, isolated feathers in amber remain of high scientific interest. The remarkable preservation of these delicate structures in amber implies a potential for significantly improving our knowledge of feather evolution and diversity. A large sample set of 150 Burmese amber specimens (Upper Cretaceous, ~99 Ma) containing feathers is herein described. Several structural types can be differentiated, including flight feathers, contour feathers, semiplumes, and filoplumes. In some cases, peculiar pigmentation patterns and structural features can be documented. Additionally, different developmental stages have been captured in this assemblage with some examples of erupting feathers or neoptile plumage. Comparisons with previous studies, including skeletal material described in amber, show that Enantiornithes and non avialan dinosaurs are most likely represented in the assemblage, as well as unknown taxa. [Display omitted] •Amber from Myanmar preserves a wide range of bird and dinosaur plumage.•Feather functions included flight, body cover, ornament, insulation, and sensory.•Amber preserves pigment patterns, growth stages, and microstructures in 3-D.